Birth Size in Neonates with Congenital Adrenal Hyperplasia due to 21-hydroxylase Deficiency - Helmuth G. Dörr; Theresa Penger; Andrea Albrecht; Michaela Marx; Thomas M. K. Völkl (JCRPE, 2019)

(untitled)
Objective:Classic congenital adrenal hyperplasia (CAH) secondary to 21-hydroxylase deficiency is characterized by increased prenatal adrenal androgen secretion. There are a small number of reports in the literature showing higher birth weight and length in CAH newborns.Methods:We analyzed birth weight and length data of 116 German newborns (48 boys, 68 girls) with classic CAH who were born during the period from 1990 to 2017. All children have been followed or are currently treated as outpatients in our clinic. All children were born at term. The mothers were healthy and their pregnancies were uneventful. The diagnosis of CAH was confirmed by molecular analyses of the CYP21A2 gene. Birth data were calculated as standard deviation (SD) scores according to German reference values.Results:Weight and length in male CAH newborns (mean ± SD) (3601±576 g; 52.4±2.85 cm) were significantly higher than in female CAH newborns (3347±442 g; 51.2±2.55 cm), but male-female differences in the CAH cohort were lost when the data were converted into SD scores. The birth sizes of the CAH newborns did not differ from the reference group. The birth sizes also did not differ between the different CAH genotypes. Maternal age, mode of delivery and maternal parity had no influence on birth size.Conclusion:Our data show that prenatal hyperandrogenism does not affect fetal growth.